PENGARUH BEBAN KERJA, WORK-FAMILY CONFLICT DAN JOB INSECURITY TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP TURNOVER INTENTION DI PT BINABUSANA INTERNUSA SEMARANG - Udriyah Udriyah; Riyadi Riyadi; Rara Ririn Budi Utaminingtyas (Politeknik Negeri Semarang, 2017)
Turnover intention is affected by many factors. The objective of this research is to analyze theinfluence of workload (X1), work-family conflict (X2), and job insecurity (X3) on job satisfaction(Y) and the impact on turnover intention (Z) partially and simultaneously. The method ofcollecting data are questionnaire, interview, observation, and documentary study. The amount ofsample is 100 production department employee. Path analysis is used in analyzing this research.The result shows that workload, work-family conflict, and job insecurity partially havenegatively and significantly influence on job satisfaction and also have simultaneouslysignificant influence on job satisfaction. Workload, work-family conflict, and job insecurity givecontributions to job satisfaction of 41,1% while 58,9% were influence by others variables. Whilejob satisfaction partially have negatively and significantly influence on turnover intention.Workload, workfamily conflict, and job insecurity partially have positively and significantlyinfluence on turnover intention and also have simultaneously significant influence on turnoverintention. Workload, work-family conflict, job insecurity, and job satisfaction give contributionsto turnover intention of 62% while 38% were influence by others variables